Measuring and analyzing the relationship between population growth and economic growth in Iraq for the period (2004-2018) using the ARDL model (Entrepreneurship Journal for Finance and Business, 2021)
Developing countries in general and Arab countries in particular suffer from high population growth, and that these population increases exert a great influence and pressure on the available economic and financial resources, This leads to imbalances in the structure of society, which may be accompanied by a kind of inequality and demolition in the value system of those societies, if it is not accompanied by an increase in investment and employment and the creation of new incomes that are redistributed in a way that reduces social differences, increases the domestic product and then economic growth . The study aims to measure the effect of the relationship between population growth and economic growth by using the (ARDL) model. The study concluded that the effect of population growth is positive on economic growth during the study period. The study recommends giving attention to the labor force and employing it in the production process in a way that reduces societal disparities and enhances economic growth.